Local Taxation, Fiscal Federalism, and the Leviathan Hypothesis: A Meta-Analytical Review of Theory and Evidence - Lakhlifi, Mounir; Belkasseh, Mohammed; Aissaoui, Safae (Archives of Business Research, 2025)
This paper examines the extent to which decentralization and intergovernmental competition constrain the revenue-maximizing behavior of governments as postulated in the Leviathan model. Building on the classical contributions of Ricardo and the subsequent national traditions of fiscal doctrine, as well as the modern welfare-based frameworks of Kaplow and Cochrane, we situate the Leviathan hypothesis within the broader literature of fiscal federalism and taxation theory. We conduct a structured meta-analysis of spatial dependence (ρ) in local tax setting. The synthesis reveals systematic evidence of positive spatial autocorrelation in property and income taxation, with coefficients clustering between 0.3 and 0.6, while motor vehicle and business taxes exhibit negligible or inconsistent effects. These findings confirm that competitive pressures constrain Leviathan governments most effectively when tax bases are both visible and territorially fixed. At the same time, the analysis highlights the role of partisan alignment in amplifying mimicking behavior, indicating that interdependence does not always translate into fiscal discipline. The policy implications are twofold: at the subnational level, decentralization enhances accountability through competitive benchmarking; at the supranational level, however, the taxation of mobile bases requires coordination to prevent harmful competition and revenue erosion. In sum, the paper integrates theoretical, empirical, and normative perspectives into a unified account of local taxation, fiscal federalism, and the constraint of Leviathan.